Replacement of soybean meal with lupine in Barbarin lamb diet: Effect on intake, digestion, fermentation and growth - Arfaoui H.; Ben Salem H.; Nasri S.; Mezni M.; Abidi S. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
This study aims to evaluate the effect of white lupine seeds as a substitute for soybean meal in the diets of lambs Twenty-four 6 and a half month-old Barbarine lambs (average initial weight 23 kg) were divided into three equal groups. Three types of concentrates, the first two of which were iso-nitrogenous, were formulated as follows: CC1 containing 75% barley, 22.5% soybean meal and 2.5% mineral and vitamin supplement (CMV); CC2 containing lupin as a substitute for soybeans; and CC3 containing only barley and CMV (this is the concentrated 1 devoid of soybean meal). In addition to the hay that was distributed at libitum, animals assigned to the first and the second group received daily, 500 g of concentrate 1 and 500g of concentrate 2, respectively. Those assigned to the third one received alternately concentrate 2 (day1) and concentrate 3 (day2). Experiment period was divided in a growth period (80 days) followed by a digestible period (10 days). Diet had no significant effect on total dry matter and water intakes, average daily gain, diet digestibility and microbial synthesis (P > 0.05). For the nitrogen balance, the animals showed different retained nitrogen level (P < 0.05). Fermentation parameters were not affected by protein source. However, only the number of protozoa was influenced by the day of fluid collection (P < 0.05). It can be concluded that lupine grains can substitute safely soybean meal in diets of Barbarine lambs.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)